Analisis Pembelajaran Remedial dan Pengayaan Pelajaran Matematika Kelas IV UPTD SD Negeri 30 Parepare - Sukma; Syam, Natriani; Lukman (STKIP Andi Matappa Pangkep, 2024)
The purpose of this study is to identify mathematics class IV remedial and enrichment learning at UPTD SD Negeri 30 Parepare. using a qualitative descriptive research design in conjunction with a qualitative technique. The subjects is 11 student and 1 teacher. Technical method is Interviews and documentation, and analysis employed are condensation, data display, and conclusion. According to the research findings, teachers have been able to identify students' strengths and problems in remedial and enrichment learning activities, create lesson plans, implement learning activities, and administer authentic assessments. Nevertheless, some students have not yet met the completion standards. This study concludes that the teacher has completed every step. From all the learning stages that have been carried out, the results show that students' knowledge and grades in mastering the material have increased.